Values and Education for Values of Today's Youth - Lesková, Andrea; Yochanna, Miri (Journal of Education Culture and Society, 2024)
Thesis. The aim of the study is to critically reflect on the challenges and current issues of value-oriented education in relation to youth. It focuses on youth as a specific generational group, internally extremely variable, in the context of massive changes in society, especially with the increase in the importance of digital technologies and social networks in the educational process.Concept. In the published study, several perspectives on the issue overlap on the theoretical and research levels. Healthy, functioning families are at the epicentre of concern for any society that cares about its own future. One of the major problems of contemporary public life, especially after the emergence of the so-called new media, is undoubtedly the issue of raising children in a media-saturated environment. The line of thought of the study is concentrated on the responsibility for the future of the society also through the formation of the value system of the young generation, considering the potential of the family in the given context.Results and conclusion. The study captures the essence, specifics, and selected aspects of insight into value-oriented youth education in the context of contemporary society. The present analysis is based on the knowledge of several scientific disciplines and its interdisciplinary character allows to look at the mentioned issue through the prism of one's own scientific field. The conclusion of the study highlights the irreplaceable importance of values education for youth, based on the central idea that values are the fundamental pillar of any society's development. It calls for values education, which is primarily the task and responsibility of the family or parents, pointing to authenticity and the need to preserve unity of thought, word and deed in a given context. Considering the dynamically changing times with an emphasis on value pluralism, as well as the tremendous growth of digital technologies, the study is a beneficial contribution to the social science discourse on values education in relation to children and youth, especially family education, which is of fundamental, formative importance for the individual.